2013
DOI: 10.1097/01.sa.0000425550.59990.25
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Impact of Dexmedetomidine Administration in 15,656 Noncardiac Surgical Cases

Abstract: RERERENCES1. Broomhead RH, Marks RJ, Ayton P. Confirmation of the ability to ventilate by facemask before administration of neuromuscular blocker: a noninstrumental piece of information? Br J Anaesth. 2010;104:313Y317.2. Ellis DY, Harris T, Zideman D. Cricoid pressure in emergency department rapid sequence tracheal intubations: a risk-benefit analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 2 publications
0
11
0
1
Order By: Relevance
“…A large‐sample retrospective study by Rebecca et al . showed that patients who had received dexmedetomidine at a dose range of 0.2–0.7 μ g/kg/hour did not report a greater incidence of hypotension and bradycardia . For hypertensive patients in long‐term standard treatment (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…A large‐sample retrospective study by Rebecca et al . showed that patients who had received dexmedetomidine at a dose range of 0.2–0.7 μ g/kg/hour did not report a greater incidence of hypotension and bradycardia . For hypertensive patients in long‐term standard treatment (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine is a more recently approved agent that enables sedation whilst minimizing the risk of respiratory depression and haemodynamic complications. The impact of dexmedetomidine on outcomes after IAMT for AIS needs ongoing research [16,[29][30]. There are 3 major concerns with the use of CS and airway protection in the acute stroke patient: Patients are unlikely to be have been adequately fasted which places them at high risk of pulmonary aspiration and most patients with large cerebral artery occlusion have a degree of dysphagia and may be unable to protect their airway after stroke [31][32].…”
Section: Conscious Sedationmentioning
confidence: 99%
“…A large cohort study included 15,656 non-cardiac surgical cases, of whom 2688 received dexmedetomidine preoperatively or intraoperatively and 12,968 did not receive dexmedetomidine. There was no significant intraoperative hypotension or bradycardia with dexmedetomidine [16].…”
Section: Discussionmentioning
confidence: 85%